THE EFFECT OF NUTRITION EDUCATION CARD GAMES FOR HEALTHY ANEMIA-FREE TEENAGERS ON THE LEVEL OF KNOWLEDGE OF ANEMIA, INTAKE OF PROTEIN, VITAMIN C AND FE IN YOUNG GIRLS AT JUNIOR HIGH SCHOOL 19 BENGKULU CITY IN 2023 - Adinda Pujalestari; Yunita; Yenni Okfrianti (Proceeding B-ICON, 2023)
Anemia is a condition in which an abnormal number of red blood cells in the body is indicated by a low level of hemoglobin in the blood. Knowledge is the result of knowing after feeling a certain object. Protein is an important nutrient for the human body because it is a source of energy, material and regulator. Intake of vitamin C is an aid in the production of hemoglobin and the growth of red blood cells. Fe is needed for the manufacture of blood plasma which produces red blood cells. Anemia Free Youth Card is a visual-based media in the form of a rectangle containing pictures, question text which serves to explain the pictures shown. This research is a Quasy Experiment research with a treatment group, through media card games, healthy adolescents free of anemia. A sample of 36 young women was taken by purposive sampling. Knowledge of young women before and after being given education through the games method with a p-value of 0.000, then p-value (<0.05), and intake of young women before and after going through a 24 hour recall with a p-value of 0.000, then p-value (<0.05). This shows that there is an influence of the Anemia-Free Healthy Teenage Card Games as a media for educating young girls about anemia in junior high schools 19 in Bengkulu City and can be used as an alternative learning media for schools to support female students in improving learning outcomes and providing adequate nutrition during growth during adolescence.